Fallout - Strasser, Todd (Candlewick Press, 2013)
When an unthinkable nuclear attack occurs in an alternate-reality 1962, Scott is forced into his father's bomb shelter with his family and neighbors, where they rapidly consume limited supplies and fear the worst about the fate of the world outside.